Can Green Bonds be a Safe Haven for Equity Investors? - Thomas Flavin; Lisa Sheenan (Queen's University Belfast, Queen's Business School, 2023)
We investigate if green bonds can act as a safe-haven asset for equity investors by analysing their relationship with stocks and other alternative safe havens, namely sovereign bonds and gold. Safe havens are defined as assets that exhibit zero or negative comovement with equity during a stock market downturn. We analyse the interrelationships between the asset classes using the Marginal Expected Shortfall of Acharya et al. (2017) and by comparing the regime-dependent GIRFs from a Markovswitching VAR model. Our results suggest that green bonds are not safe haven assets for equity investors but rather show positive comovement during periods of market stress. The sovereign bond is the most consistent in delivering diversification benefits across market conditions, while gold acts as a safe-haven asset during all regimes except during rare periods of extreme turbulence.
Keywords: C15; C34; Q56; 330; Green bonds; Contagion; Financial crisis; Markov-switching VAR